A cross sectional study to assess prediction of microalbuminuria using neutrophilto- lymphocyte ratio and red blood cell distribution width in diabetic patients - Manoj Kumar Bind; Mayank Kumar; Archana Singh; Vinod Kumar; Dhananjay Kumar Singh (Asian Journal of Medical Sciences, 2023)
Background: This study was devised to evaluate the predictive value of neutrophilto- lymphocyte ratio (NLR), mean platelet volume (MPV), and red blood cell distribution width (RDW) to detect microalbuminuria in type 2 diabetic patients. This can help in early detection of microalbuminuria and assessment of prognosis inn patients suffering from type 2 diabetes mellitus (DM). Aims and Objectives: The objectives of the study were to assess the diagnostic accuracy of microalbuminuria using neutrophil-to-lymphocyte ratio and red blood cell distribution width in diabetic patients. Materials and Methods: A total of 188 patients with type 2 DM were selected for this study. Subjects were classified into three groups based on hemoglobin A1c and microalbuminuria. Group A had 63 patients with controlled diabetes, Group B had 62 patients with uncontrolled diabetes, both without microalbuminuria, and Group C had 62 patients with uncontrolled diabetes with microalbuminuria. Levels of NLR, MPV, and RDW between the study groups were analyzed. Results: A significant difference in NLR was found between Group C and Groups A and B (P<0.001 and P=0.005, respectively). RDW was significantly different between Groups B and C (P=0.014). Receiver operating characteristic curve analysis was done between NLR and RDW. The area under curve was found to be of 0.678 for NLR (confidence interval: 0.59–0.75, P<0.001) and 0.616 for RDW (confidence interval: 0.49–0.73, P=0.013). The study shows that an NLR cutoff point of 2.54 has 39.7% sensitivity, 78.8% specificity, and 45% positive predictive value (PPV). An RDW cutoff point of 14.44 has 37.9% sensitivity, 76% specificity, and 41.5% PPV. Conclusion: NLR and RDW can be beneficial to detect microalbuminuria in diabetic patients.